A preboreal elk (Alces alces L., 1758) antler from south-eastern Norway - Grøndahl, Finn Audun; Hufthammer, Anne Karin; Dahl, Svein Olaf; Rosvold, Jørgen (Fauna norvegica, 2016)
In 1895 a shed elk antler was found in a mire on a farm near Fluberg, in Søndre Land municipality in south-eastern Norway. The antler was first radiocarbon dated in 2008 and yielded the age 9,100 ± 50 BP (8,340 – 8,250 BC), which is the oldest dated elk remain from Norway. Elk (Alces alces L., 1758) are a pioneer colonising species; they were already established south of the ice front in Denmark and southern Sweden in the Late Glacial period. This antler shows that the species had arrived in south-eastern Norway in the late Preboreal period. This could tie in with the earliest arrival of elk once the colonizing routes from southern Sweden were established 9,300-9,200 BP. The antler is clearly of the palmate morph, and strongly resembles elk antlers found in Denmark and southern Sweden from the Late Glacial and Early Holocene periods. This find also reveals that the vegetation at the end of the Preboreal period suited large herbivores such as elk publishedVersion